Salidroside can protect against ferroptosis in cardiomyocytes and may be related to the regulation of GGT1 - Feng, Tianhang; Shi, Jing; Zhao, Jinghua; Zhao, Qin; Wang, Tao; Wan, Sha; Fan, Chen; Wang, Sijia; Lai, Chunyou; Yao, Yutong (Frontiers in Pharmacology, 2025)
IndroductionFerroptosis, an iron-dependent cell death mechanism driven by lipid peroxidation, represents a novel therapeutic target for myocardial injury. Salidroside (SAL), a natural bioactive compound derived from Rhodiola rosea, exhibits cardioprotective effects through multi-target mechanisms with minimal adverse effects, yet its precise role in ferroptosis regulation remains unclear.MethodsThis study systematically investigated SAL’s anti-ferroptotic effects using in vitro (RSL3-induced H9C2 cardiomyocytes) and in vivo (DOX-induced myocardial injury mouse model) approaches.ResultsSAL treatment significantly enhanced cardiomyocyte viability by attenuating ferroptotic hallmarks, including lipid ROS accumulation, iron overload, lipid peroxidation, and mitochondrial dysfunction. Transcriptomic analysis revealed SAL-mediated modulation of DNA replication/repair, cell cycle regulation, protein autophosphorylation, drug ADME processes, and glutathione metabolism—a critical pathway in ferroptosis. Molecular docking identified γ-glutamyltransferase 1 (GGT1) as a high-affinity SAL target, linking drug metabolism and glutathione homeostasis. In MI mice, SAL downregulated GGT1 expression while restoring ferroptosis-related biomarkers: upregulating GPX4 and reducing SLC7A11/LC3II levels. Mechanistically, SAL suppresses ferroptosis through dual regulation of GGT1: (1) enhancing glutathione synthesis via GGT1 inhibition and (2) potentiating GPX4-mediated antioxidant defense.DiscussionThese findings establish GGT1 as a pivotal therapeutic target for SAL’s cardioprotection, providing a mechanistic basis for its clinical application in ferroptosis-associated cardiovascular diseases.